Lessons from surgical outcome for intracranial meningioma involving major venous sinus. Issue 35 (August 2016) - Han, Moon-Soo; Kim, Yeong-Jin; Moon, Kyung-Sub; Lee, Kyung-Hwa; Yang, Jung-In; Kang, Woo Dae; Lim, Sa-Hoe; Jang, Woo-Youl; Jung, Tae-Young; Kim, In-Young; Jung, Shin
Abstract : Abstract: Intracranial meningiomas involving the major venous sinus (MVS) pose several complication risks upon performing radical resection. Some surgeons consider MVS invasion a contraindication for a complete resection of meningioma, and others suggest total resection followed by venous reconstruction. The aim of the study was to analyze our surgical results and discuss management strategy for intracranial meningiomas involving the MVS. Between 1993 and 2011, 107 patients with intracranial meningiomas involving MVS underwent surgery in our institution. Clinicoradiological features including pathological features and operative findings were retrospectively analyzed. Median follow-up duration was 60.2 months (range, 6.2–218.2 months). Distributions of tumor cases according to the involved sinus were as follows: 86% parasagittal, 10.3% tentorial, and 3.7% peritorcular. Simpson Grade I/II removal was achieved in 93 of 107 patients (87%). Partially or totally occluded MVS by their meningiomas (Sindou classification IV and V) was found in 39 patients (36%). Progression rate was 12% (13/107) and progression-free survival rates were 89%, 86%, and 80% at 5, 7, and 10 years, respectively. Sindou classification (IV/V) and Karnofsky performance status (KPS) score 6 month after the surgery (KPS < 90) were predictive factors for progression in our study ( P = 0.044 and P = 0.001, respectively). The resection degree did not reach statistical significance ( P = 0.484). Interestingly, there was no progression in patients that underwent radiation therapy or gamma knife radiosurgery for residual tumor. There were no perioperative deaths. Complication rate was 21% with brain swelling being the most common complication. There was no predictive factor for occurrence of postoperative complication in this study. In conclusion, complete tumor resection with sinus reconstruction did not significantly prevent tumor recurrence in intracranial meningioma involving MVS. Considering the complications from this procedure as it has possibly related with reduced postoperative KPS score, the tumor should be removed as much as possible while leaving remnant portion with significant invasion of sinus or drainage vein. Following radiation therapy or gamma knife radiosurgery for a remnant or recurred meningioma might then be justified.